2014
DOI: 10.1016/j.jgr.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ginsenosides in different tissues after elicitor treatment in Panax ginseng

Abstract: BackgroundThe effect of methyl jasmonate (MJ) on ginsenoside production in different organs of ginseng (Panax ginseng Meyer) was evaluated after the whole plant was dipped in an MJ-containing solution. MJ can induce the production of antioxidant defense genes and secondary metabolites in plants. In ginseng, MJ treatment in adventitious root resulted in the increase of dammarenediol synthase expression but a decrease of cycloartenol synthase expression, thereby enhancing ginsenoside biosynthesis. Although a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Next finding was that a certain hypothermic stimulation could promote the accumulation of active components. Oh et al () found that all total ginsenosides content in different organs from 1‐year‐old root increased after treatment at 4°C. Similarly, the level of genistein in Glycine max.…”
Section: Discussionmentioning
confidence: 99%
“…Next finding was that a certain hypothermic stimulation could promote the accumulation of active components. Oh et al () found that all total ginsenosides content in different organs from 1‐year‐old root increased after treatment at 4°C. Similarly, the level of genistein in Glycine max.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations have revealed that a large portion of the intact ginsenosides can be transformed into minor ginsenosides with more enhancing biological effects through gastrointestinal acids, enzymes, and intestinal bacteria, especially by β-glucosidase enzymes in human intestine (Christensen, 2009), therefore the enzymatic methods have been used to obtain minor ginsenosides. Recently, several studies have succeeded to conduct scale-up engineering for the bioconversion using a recombinant enzymes, particularly for ginsenoside Rg3 (Chang et al, 2009;Kim et al, 2013c;Oh et al, 2014b;Shin et al, 2014;Quan et al, 2012;2013) (Table 2). However, due to the limited availability of ginsenosides for large scale compound K production, and the challenge of chemical synthesis caused by the difficulty of selective glycosylation of ginsenosides, other approaches have been explored.…”
Section: Engineered Yeast Cellsmentioning
confidence: 99%
“…Therapeutic effects of P. ginseng on neurodegenerative disorders (Cho, ; Radad et al ., ), cardiovascular diseases (Zheng et al ., ), diabetes (Xie et al ., ) and cancer (Jung et al ., ; Wong et al ., ) are often attributed to unique saponins called ginsenosides, glycosylated triterpenes classified as either dammarane‐ ( Panax ‐specific) or oleanane‐type based on aglycone skeletal structure. Ginsenosides are accumulated in roots, leaves, stems, flower buds and berries, in quantities varying with tissue (Oh et al ., ; Shi et al ., ), age (Shi et al ., ; Xiao et al ., ), environment (Jiang et al ., ; Kim et al ., ) and cultivar (Lee et al ., ). Limited genomic resources and genetic populations due to slow growth (~4 years/generation), sensitivity to environmental stresses and low seed yield (40/generation) hamper developmental and genetic studies and breeding.…”
Section: Introductionmentioning
confidence: 98%